2008
DOI: 10.1002/jmri.21342
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based diffusion tensor magnetic resonance imaging evaluation of low‐grade hepatic encephalopathy

Abstract: Purpose: To quantify the changes in brain water diffusivity in hepatic encephalopathy (HE) associated with cirrhosis using diffusion tensor imaging (DTI) and to correlate with neuropsychological (NP) scores. Materials and Methods: DTI was performed in 14 patients with low-grade HE and age/gender-comparable 16 healthy controls. Whole brain mean diffusivity (MD) and fractional anisotropy (FA) maps were calculated, normalized to common space, smoothed, and compared voxel-by-voxel between groups using analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 32 publications
6
40
0
Order By: Relevance
“…Cerebral edema from hepatic encephalopathy is associated with increased MD and variable changes in FA. 21,22 After lactulose therapy for hepatic encephalopathy, MD decreased while FA did not change. 22 Peritumoral edema shows both a decrease in FA and an increase in apparent diffusion coefficient (which is comparable with MD).…”
Section: Description Of the 21 Patients With Msmentioning
confidence: 99%
“…Cerebral edema from hepatic encephalopathy is associated with increased MD and variable changes in FA. 21,22 After lactulose therapy for hepatic encephalopathy, MD decreased while FA did not change. 22 Peritumoral edema shows both a decrease in FA and an increase in apparent diffusion coefficient (which is comparable with MD).…”
Section: Description Of the 21 Patients With Msmentioning
confidence: 99%
“…16 In addition, positron-emission tomography studies have indicated that an altered glial cell state, an important cause of MHE, occurs in the frontal WM and in the corpus callosum. 36 The frontal and parietal WM and corpus callosum (particularly the anterior part) are the regions most commonly reported to demonstrate increased water content 11 or diffusivity 9,10,12,15,16 and decreased FA. 15 When patients with cirrhosis in the intermediate state are excluded, Sugimoto et al 16 reported 70%-90% sensitivity and 85%-90% specificity in classification of MHE and NHE, based on a frontal or parietal WM ADC metric.…”
Section: Results Of Gamma Analysismentioning
confidence: 99%
“…One limitation of our study is that we confined our analysis to WM regions, where brain edema predominantly occurs in MHE 11,15 ; however, several studies have indicated that other cerebral regions, such as subcortical nuclei, 9,10 may also manifest low-grade edema. The second limitation is that we used a suboptimal DTI sequence with 6 diffusion-encoding gradient directions, due to the finite capability of our MR imaging scanner.…”
Section: Results Of Validation Analysismentioning
confidence: 99%
See 2 more Smart Citations